2021
DOI: 10.1590/2318-0331.262120210043
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical characterization of reservoir waters undergoing salinization processes in Northeastern Brazil

Abstract: The geochemical processes that potentially control the chemical characteristics of the waters of three reservoirs located in the state of Sergipe, Northeastern Brazil, were evaluated using the Gibbs diagram, correlation analysis, ionic ratios and geochemical modeling. The results of the reverse geochemical modeling applied between two water samples from each reservoir were in agreement with the observations of the correlation analysis and ionic ratios, which indicated sea salt dissolution, silicate weathering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The value of A for the samples ranged from -8.5% to 3.7% with an absolute mean value of 3.5% for the Algodoeiro reservoir, from -4.7% to 2.5% with an absolute mean value from 2.1% for Três Barras and from -5.5% to -5.2% with an absolute mean value of 3.7% for Glória. These values are in agreement with the absolute mean values reported by Merchán et al (2015), which ranged from 2.5% to 4.4% when assessing salinization in an irrigation basin in Spain, and with the absolute mean values indicated by Alves et al (2021), which ranged from 2.5% to 3.0% when evaluating reservoirs undergoing salinization in Northeastern Brazil. According to El Yaouti et al ( 2009), a ± 10% error in the ion balance is acceptable for this type of study.…”
Section: Sampling and Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…The value of A for the samples ranged from -8.5% to 3.7% with an absolute mean value of 3.5% for the Algodoeiro reservoir, from -4.7% to 2.5% with an absolute mean value from 2.1% for Três Barras and from -5.5% to -5.2% with an absolute mean value of 3.7% for Glória. These values are in agreement with the absolute mean values reported by Merchán et al (2015), which ranged from 2.5% to 4.4% when assessing salinization in an irrigation basin in Spain, and with the absolute mean values indicated by Alves et al (2021), which ranged from 2.5% to 3.0% when evaluating reservoirs undergoing salinization in Northeastern Brazil. According to El Yaouti et al ( 2009), a ± 10% error in the ion balance is acceptable for this type of study.…”
Section: Sampling and Analysissupporting
confidence: 89%
“…They also highlighted that the local geology favors silicate weathering as the most likely cation and bicarbonate source. Alves et al (2021), when assessing reservoirs undergoing increasing salinization processes in northeastern Brazil, also concluded that atmospheric transport and silicate were the main geochemical processes responsible for the chemical characteristics of the waters of the investigated reservoirs, with a smaller contribution to carbonate dissolution. Wisitthammasri et al (2020) indicated that the fact that they did not observe a relationship between (Ca 2+ + Mg 2+ ) with HCO 3 -, in agreement with the theoretical range predicted for carbonate dissolution, is an indication that water hydrochemistry in the Province of Saraburi/Thailand is consistent with silicate minerals.…”
Section: Reservoir Hydrogeochemistrymentioning
confidence: 86%
See 1 more Smart Citation
“…During the direct ion exchange reaction, Na + (± K + ) ions from the surface of clay minerals are displaced by Ca 2+ (± Mg 2+ ) ions present in the water, resulting in the enrichment of water in Na + (± K + ) (Alves et al 2021). Direct ion exchange with clay materials is generally observed when water is being salinized (Slama & Bouhlila 2017).…”
Section: Hydrogeochemistrymentioning
confidence: 99%
“…In this context, Gomes and Franca (2019) state that the studying the groundwater chemistry can provide information on anthropogenic interference and dissolution/precipitation processes. Water salinization, a frequent problem in northeastern Brazil, can affect freshwater reservoirs, and poses a risk for human health and to many natural systems (Alves et al 2021). The literature (Fontes et al 2015;Guo et al 2018;Jia et al 2020) highlights that salinization occurs as a function of climatic conditions, reservoir age, rock solubility, marine aerosol deposition, etc.…”
Section: Introductionmentioning
confidence: 99%